Topical Jatropha multifida L. ointment improves perineal wound healing in postpartum mothers: a randomized controlled trial - Fera, Fitria Candra; Marsum; Sri Rahayu (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2026)
Background: Postpartum perineal wound care may lead to infection if not managed properly. Jatropha multifida L. contains various secondary metabolites that may accelerate wound healing; however, clinical evidence remains limited. Objective: This study aimed to evaluate the effectiveness of Jatropha multifida L. extract ointment compared with standard clean and dry wound care in promoting perineal wound healing. Methods: This was a true experimental study with a pre–posttest control group design. A total of 60 postpartum mothers with second-degree perineal lacerations were randomly assigned into three groups: control, 15% extract, and 20% extract. The interventions were applied twice daily for 7 days. Wound healing was assessed on days 3, 5, and 7 using the REEDA (Redness, Edema, Ecchymosis, Discharge, Approximation) score. Results: The Friedman test showed a significant reduction in REEDA scores across all groups (p < 0.001). The greatest decrease was observed in the 15% concentration group (mean = 0.4). Cohen’s d indicated a very large effect size (d = 1.835). Conclusions: Jatropha multifida L. extract ointment at a 15% concentration was effective in improving perineal wound healing in postpartum mothers.